1994
DOI: 10.1111/j.1365-2133.1994.tb04983.x
|View full text |Cite
|
Sign up to set email alerts
|

One-week therapy with oral terbinafine in cases of tinea cruris/corporis

Abstract: The use of oral terbinafine in the treatment of superficial dermatophyte infections has been extensively studied, using different treatment regimens. To evaluate the efficacy of short-term therapy with oral terbinafine in cases of tinea cruris/corporis, 22 patients (21 male and one female) with mycologically proven tinea cruris/corporis, were included in the present study. Each patient received one tablet of terbinafine 250 mg daily for 1 week. Patients were followed-up for 6 weeks after completion of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…77 While these infections typically respond to topical antifungals, oral therapy is often indicated when the lesions are widespread or chronic in nature. 78 Terbinafi ne applied topically as a 1% cream, gel or solution demonstrates utility in the management of both tinea corporis and tinea cruris. 79 The application of terbinafi ne once-daily for 7 to 14 days resulted in mycological cure rates ranging from 84% to 94%, clinical cure rates ranging from 75% to 84% and overall effi cacy rates ranging from 65% to 83%; [80][81][82][83][84][85][86] The observed treatment response with topical terbinafi ne is signifi cantly greater than reported for placebo wherein clinical, mycological and complete cure rates range from 8% to 22%.…”
Section: Cutaneous Dermatophytosesmentioning
confidence: 99%
See 1 more Smart Citation
“…77 While these infections typically respond to topical antifungals, oral therapy is often indicated when the lesions are widespread or chronic in nature. 78 Terbinafi ne applied topically as a 1% cream, gel or solution demonstrates utility in the management of both tinea corporis and tinea cruris. 79 The application of terbinafi ne once-daily for 7 to 14 days resulted in mycological cure rates ranging from 84% to 94%, clinical cure rates ranging from 75% to 84% and overall effi cacy rates ranging from 65% to 83%; [80][81][82][83][84][85][86] The observed treatment response with topical terbinafi ne is signifi cantly greater than reported for placebo wherein clinical, mycological and complete cure rates range from 8% to 22%.…”
Section: Cutaneous Dermatophytosesmentioning
confidence: 99%
“…84 Following oral administration for the treatment of tinea corporis and tinea cruris, clinical and mycological cure rates observed with terbinafi ne have ranged from 71% to 100% and 78% to 100%, respectively. 78,[87][88][89] No signifi cant differences in mycological or clinical cure rates were observed between terbinafi ne and griseofulvin in these studies; [87][88][89] however, higher relapse rates were observed with griseofulvin. 88,89 Tinea imbricata, a variant of tinea corporis found predominantly in tropical countries, manifests as concentric rings of papular plaques that are chronic in nature and relatively recalcitrant to antifungal therapy.…”
Section: Cutaneous Dermatophytosesmentioning
confidence: 99%
“…Terbinafine and itraconazole are equally effective in treating tinea corporis. 2,3 An alternative is fluconazole which is given orally once a week for up to four consecutive weeks. 4,5 Fluconazole, a synthetic triazole derivative, is an azole antifungal agent.…”
Section: Introductionmentioning
confidence: 99%
“…Terbinafine has also been shown to be very effective for the treatment of tinea corporis and tinea cruris. In a study in which 22 patients were administered terbinafine 250 mg/day for 1 week, 100% mycologic and clinical clearing was observed 6 weeks after treatment [59].…”
Section: Tinea Corporis and Tinea Crurismentioning
confidence: 99%